Case Report: A New Peroxisome Proliferator-Activated Receptor Gamma Mutation Causes Familial Partial Lipodystrophy Type 3 in a Chinese Patient - Chen, Xi; Ma, Zhiqiang; Chen, Peng; Song, Xiuli; Li, Weihua; Yu, Xuefeng; Xie, Junhui (Frontiers in Endocrinology, 2022)
Abstract Purpose: Familial partial lipodystrophy type 3 (FPLD3) is an autosomal dominant disease. Patients typically present with loss of adipose tissue and metabolic complications. Here, we reported a Chinese FPLD3 patient with a novel PPARG gene mutation. Methods: A 16-year-old female patient and her relatives were assessed by detailed clinical and biochemical examinations. Sequencing was performed by using the extracted DNA. Moreover, we identified FPLD3 patients from previous studies, and according to the protein region affected by the gene mutation. We divided the patients into the DNA-binding domain (DBD) group or the ligand-binding domain (LBD) group, and compared the clinical features between the two groups. Results: We identified a novel gene mutation affecting the LBD of PPARG c.929T > C (p.F310S). This mutation leads to the substitution of a phenylalanine by a serine. In our case, subcutaneous fat was significantly diminished in her face, hips and limbs. The patient was also presented with insulin resistance, diabetes mellitus, hypertriglyceridemia, fatty liver, liver dysfunction, albuminuria and diabetic peripheral neuropathy. After literature review, a total of 64 FPLD3 patients were identified and we found no difference in clinical features between the DBD group and LBD group (all P > 0.05). Conclusions: A Chinese FPLD3 patient with a novel PPARG gene mutation is described. Our case emphasized the importance of physical examination and genetic testing in young patients with severe metabolic syndromes.